Survival and Acid Adaptation Ability of Salmonella during Processing and Ripening of Savak tulumi Cheese - Calicioglu, Mehmet; Dikici, Abdullah (Medwell Online, 2009)
The present study was undertaken to investigate, the effect of production conditions of Savak tulumi cheese, a type of naturally fermented, semi-solid cheese made from raw ewe milk, on the survival and acid adaptation ability of Salmonella. Raw ewe milk was inoculated with a 5 strain mixture of Salmonella at a level of approximately 7.0 log(10) cfu mL(-1) prior to rennetting. Processing steps included cutting fresh curd into small pieces, pressing, breaking up and mixing with salt then holding at 25 degrees C for 3 days. Next, the resulting cheese was filled in to plastic containers and stored at 6 degrees C for 90 days for ripening. The cheese samples were taken on days 0, 1 and 2 during processing and on days 0, 15, 30, 45, 60 and 90 during ripening for chemical, microbiological analysis and acid challenge tests in synthetic gastric fluid. The results indicated that pH of the curd decreased to 4.65 +/- 0.11 by day 90 and the titratable acidity increased to 1.98 +/- 0.09 la. The numbers of Salmonella decreased significantly as of 2nd of processing and during ripening and finally dropped below detection limit (<1.0 log(10) cfu g(-1)) by day 90. In acid challenge test, in none of the sampling days, Salmonella did not survive to 90 min exposure. These results revealed that Savak tulumi cheese production yields >7.0 log reduction of Salmonella and the resulting intrinsic environment during production do not allow the pathogen to develop any resistance to the acid.
Keywords: Salmonella; tulumi cheese; ripening; acid resistance; synthetic gastric fluid